2019
DOI: 10.3906/vet-1904-20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breeder age on egg quality and lysozyme activity

Abstract: The research material consisted of eggs bought from parent stock of Ross 308 meat chickens. The birds were kept on deep litter in enclosed housing (Borzychy, Masovian Voivodeship, Poland) in accordance with the requirements given in "Instructions for Raising a Ross 308 Flock" [16]. The microclimate conditions of the chicken houses were strictly controlled in accordance with accepted standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(39 reference statements)
5
10
1
Order By: Relevance
“…These traits are influenced by both hen genotype and age, which means that these factors indirectly affect lysozyme content and activity. Banaszewska et al (2019), who studied the eggs of broiler breeder hens, observed a significant increase in lysozyme activity in the eggs from older hens, which is consistent with our study. In turn, Kowalska et al (2020) reported that diet compared to hen's age had a greater effect on this trait.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These traits are influenced by both hen genotype and age, which means that these factors indirectly affect lysozyme content and activity. Banaszewska et al (2019), who studied the eggs of broiler breeder hens, observed a significant increase in lysozyme activity in the eggs from older hens, which is consistent with our study. In turn, Kowalska et al (2020) reported that diet compared to hen's age had a greater effect on this trait.…”
Section: Discussionsupporting
confidence: 92%
“…A higher level of lysozyme in the albumen of eggs from commercial layer hybrids, compared to our study, was also reported by Lewko and Gornowicz (2015). In the study by Banaszewska et al (2019), lysozyme activity in the eggs of Ross 308 broilers was considerably lower than in our study.…”
Section: Discussioncontrasting
confidence: 82%
“…The age of hens had a greater effect on the concentration and activity of lysozyme in the eggs than on shell quality traits, and our results are consistent with the findings of Banaszewska et al. (2019) .…”
Section: Discussionsupporting
confidence: 90%
“…This lower buffering capacity is related to the easier CO 2 loss from the albumen [ 32 ], which is related to a more rapid release of CO 2 through the eggshell. This phenomenon is the consequence of a higher eggshell conductance (due to its lower eggshell quality) in eggs from older hens [ 33 , 34 ] that results from the decrease of the eggshell thickness with the increase of the breeder age [ 26 ]. The lower buffering capacity will finally result in faster increase of albumen pH [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in negative effects of prolonged egg storage with breeder age are probably related to changes in the embryo (e.g., number of viable cells) or egg characteristics (e.g., albumen pH and viscosity, shell quality), or in both of them [ 25 , 26 ]. As shown above, the interaction between storage duration and breeder age varies between studies; for review see Nasri et al [ 27 ].…”
Section: Introductionmentioning
confidence: 99%